Use of Lighting Equipment in Terms of Urban Landscape Designs; Example of Yozgat Sports Valley - Kübra YAZİCİ and Selin TEMİZEL (ISPEC Journal of Agricultural Sciences, 2020)
Equipment elements are structural elements which support social activities in urban landscape areas. Due to its versatile functionality, the equipment elements increase the environmental quality and contribute to the urban identity. Today, urban areas need ergonomic, aesthetic and well-maintained equipment elements that are properly designed. In other words, people who are stuck between concrete structures in the city need recreational areas surrounded by comfortable safe building elements that they can feel belonging to.The fact that lighting equipment elements supports all equipment elements aesthetically and functionally. In this context, it is a recreational area, which is located in the region where Yozgat has the most intense circulation, and is used extensively by the people of the city. The aim of this study was to examine the current status of the lighting equipment elements used in the Sports Valley, where was a part of the daily city and actively used by the public, in terms of landscape design. As a result of the data obtained, suggestions were made for improvement studies to be carried out in Sports Valley and the suitability of the lighting equipment elements in the study area was evaluated by Q-SORT analysis in terms of landscape design